2012
DOI: 10.1111/j.1447-0756.2012.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive rectal misoprostol versus oxytocin infusion for prevention of postpartum hemorrhage in women at risk: A randomized controlled trial

Abstract: Rectal misoprostol is as effective as oxytocin infusion as an adjunct for prevention of postpartum hemorrhage in women with risk factors for uterine atony and is associated with a lower hematocrit drop and blood transfusion postpartum. However, shivering, pyrexia and vomiting are more frequent with misoprostol, though usually self-limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
7
8
1
Order By: Relevance
“…The incidence of PPH in the misoprostol group was 19.6% which was similar to 18.5% observed in the oxytocin group and comparable with 22.2% Versus 20.9% respectively reported by Badejoko et al in South West Nigeria. 17 This study demonstrated that there was no significant difference in the incidence of PPH in both groups and is also comparable to findings from previous quoted-study 17…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The incidence of PPH in the misoprostol group was 19.6% which was similar to 18.5% observed in the oxytocin group and comparable with 22.2% Versus 20.9% respectively reported by Badejoko et al in South West Nigeria. 17 This study demonstrated that there was no significant difference in the incidence of PPH in both groups and is also comparable to findings from previous quoted-study 17…”
Section: Discussionsupporting
confidence: 90%
“…The higher incidences of PPH recorded in our study as well as in the earlier study conducted in Nigeria utilizing adjunctive uterotonics after AMTSL17 affirms the magnitude of PPH in Nigeria to be high. This finding suggests that the incidence of PPH may have been much higher in this obstetric population in the absence of adjunctive uterotonics since all the patients had AMTSL.…”
Section: Discussionsupporting
confidence: 82%
“…Elbourrne et al 13 reported significant reduction of the amount of blood loss when prophylactic administration of uterotonic agents during the third stage of labor. Similarly Badejoko et al 14 reported dramatic effect of rectal misoprostol (600 lg) in prevention of PPH comparable with oxytocin infusion.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Kessous et al ( 9 ) reported that bleeding accounted for 70% of indications for relaparotomy. Bleeding secondary to uterine atony is preventable by adopting active management of the third stage of labor in women with identifiable risk factors for uterine atony by either rectal misoprostol or oxytocin infusion ( 10 ). Intra-abdominal bleeding after CS depends on the skill and the experience of the operator and the surgical technique used, such factors would be difficult to discern in the current study, because this essential parameter was not evaluated.…”
Section: Discussionmentioning
confidence: 99%